Liquid marble clearance and restoration via gas bubble insertion and bursting. Issue 9 (28th January 2021) - Lin, Eric Shen; Song, Zhixiong; Ong, Jian Wern; Abid, Hassan Ali; Chung Kim Chung, Dwayne; Huynh, So Hung; Liew, Oi Wah; Ng, Tuck Wah
Abstract : The introduction of a gas bubble is a simple way to disrupt the apical coating of particles on liquid marbles to introduce additional reagents. Abstract : There is hitherto a lack of a simple way to disrupt the coating of particles from liquid marbles in order to introduce additional reagents. Here, a 40 μL liquid marble, created on a superhydrophobic substrate with a 2 mm hole, forms an overhead and overhanging liquid component from which a single gas bubble of up to 28 μL volume could be introduced via the latter. This caused a localized clearing of the particle shell at the apical region of the overhead component because the particles could not be energetically sustained at the thin film region of the bubble. The subsequent dispensation of 5 μL of an external liquid directly onto the shell-free apex of the liquid marble allowed the coalescence of the two liquid bodies, bubble rupture, and restoration of complete particle shell encapsulation. The addition of the liquid via the overhanging component was alternatively found incapable of increasing the size of the overhead drop component. The localized bubble-actuated transient shell clearance at the apex of the liquid marble to allow the addition of reagents shown here portends new vistas for liquid marbles to be used in biomedical applications.